Political Strategies of Members of Clubs and Associations in Oral History Research - Hlaváček , Jiří; Horáková, Monika (Dějiny – teorie – kritika, 2013)
The aim of this study is to use two examples of oral history research (studies which focused on two organised social groups, namely the Sudetendeutsche Landsmannschaft and Czech Military Rehabilitated Persons Association) in order to analyse a tension between the particular experience of narrators and the political rhetoric of association to which they belong. Th ough the orientation and development of the two abovementioned organisations has been markedly different, one can trace a certain analogies in the narratives of their members. The authors’ starting assumption is that in order to achieve their political goals, organised social groups use currently shared notions of the past and adjust their rhetoric correspondingly. Narrators who openly claim allegiance to groups with clearly defined goals then consciously or unconsciously use various narrative strategies and patterns in order to project these aims into their interviews. The study outlines idealised models of these strategies, which can be detected on four main levels: conceptual, historical, social, and institutional. In the final part of the study, the authors formulate general conclusions applicable to oral history research of other politically organised groups whose establishment is explicitly based on a particular historical event.